IgG4‐related disease in patients with idiopathic orbital inflammation syndrome: data from the French SIOI prospective cohort. Issue 4 (12th November 2018) - Abad, Sébastien; Martin, Antoine; Héran, Francoise; Cucherousset, Nahla; Mouriaux, Frédéric; Héron, Emmanuel; Sédira, Neila; Zmuda, Mathieu; Groh, Matthieu; Abbas, Aïcha; Saadoun, David; Aucouturier, Pierre; et al.
Abstract: Purpose: To better characterize IgG4‐related disease (RD) in the setting of idiopathic orbital inflammation syndrome (IOIS). Methods: National, multicentre, prospective, observational cohort study. Among the patients consecutively included in the French multicentre SIOI cohort, we selected those who underwent orbital and/or adnexal biopsy. Clinical, morphological and pathological findings at diagnosis were blindly analysed. Serum IgG4 levels at inclusion were measured and all available biopsy specimens were immunostained for IgG4 and IgG. Biopsy samples with more than 10 IgG4‐positive plasma cells per high‐power field and a IgG4+/IgG+ plasma cell ratio above 40% were scored as positive. IgG4‐positive patients were then screened for comprehensive diagnostic criteria for IgG4‐RD. Results: Of the 87 patients included, 35 had histologically documented IOIS. Thirteen patients (37%) with a mean age at onset of 27 years (range 21–78) had IgG4‐positive biopsies, among which 10 patients (77%) and 3 (23%, with IgG4 serum levels >1.35 g/L) were considered as having probable and definite IgG4‐RD, respectively. The latter 13 patients more frequently fulfilled histological criteria for IgG4‐RD (including plasmacytic infiltrate (p = 0.006), fibrosis (p = 0.0025) and periphlebitis (p = 0.075)) than IgG4‐negative patients. Storiform fibrosis was exclusively found in orbital tissues from IgG4‐positive patients ( n = 3, 23%). Eosinophilia associated with recurrent sinusitis or asthma was a prominent feature in patients with definite IgG4‐RD. Conclusions: More than one‐third of patients with biopsy‐proven IOIS satisfied criteria for IgG4‐RD, but only a few had a definite type.